Interpretation of fatwa during Covid-19 in Sabah (2019-2021) - Ahmad Tarmizi Abdul Rahman; Nor-Ina Kanyo; Nurul A’fifah Muarifin Sufianto (Academia Industry Networks, 2022)
Fatwa is recognized as one of the sources of the Islamic Law in Malaysia. In some cases, the fatwa is used as a reference to the Syariah Court in resolving Islamic dispute and legal problem. This study attempts to look at the implicit meanings that can be interpreted in the scope of fatwa throughout the duration of the Covid-19 pandemic. Various tenets in the Islamic traditions have changed during the pandemic, especially in worship activities. Therefore, this study was conducted on 50 Muslim respondents around the city of Kinabalu and it suburbs The data were analyzed using the Statistical Package of Social Sciences (SPSS) and presented in the form of frequency and percentage (demography study). This study focused on a group of informants from JAKIM, JHEAINS, some Imams, and people to answer the questionnaire distributed. The results of the study found that the community still believes in the importance of the concept of practicing spiritual elements (Sufism) in mosques and suraus. At the same time, the respondents also agreed that the restrictions and prohibitions from the government and the National Fatwa Community Council are to protect the health of the public from Covid-19.